2011
DOI: 10.1111/j.1365-2788.2011.01455.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparing residential programmes for adults with autism spectrum disorders and intellectual disability: outcomes of challenging behaviour and quality of life

Abstract: Background Owing to methodological issues, little research has been conducted to examine quality of life (QoL) as a treatment outcome in autism spectrum disorders (ASD) and intellectual disabilities (ID). This study was conducted to combine QoL measures and objective observations of challenging behaviours (CB) in order to evaluate changes over time in adults with ASD and ID who were treated in two different residential programmes; we hypothesised that a decrease in CB would be related to an improved QoL. Metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(30 citation statements)
references
References 64 publications
0
28
0
Order By: Relevance
“…The classification of autism and the severity of the disorder are important factors in the assessment of quality of life . One of the limitations of this study is that because of the reliance on school records for the diagnosis of autism, the classification and assessment of severity were not captured with the desired degree of accuracy.…”
Section: Discussionmentioning
confidence: 98%
“…The classification of autism and the severity of the disorder are important factors in the assessment of quality of life . One of the limitations of this study is that because of the reliance on school records for the diagnosis of autism, the classification and assessment of severity were not captured with the desired degree of accuracy.…”
Section: Discussionmentioning
confidence: 98%
“…Improved quality of life is increasingly a primary goal of interventions and services for adults with ASD (Gerber et al, 2011), making accurate assessment of this construct critical for research and clinical practice. Measuring the validity of self-report is complex when it comes to quality of life, however.…”
Section: Quality Of Lifementioning
confidence: 99%
“…Similarly, of 18 peer-reviewed articles identified reporting on results from longitudinal studies of adults with ASD, 15 articles drew on data from participants initially recruited in childhood. The remaining three studies had recruited adult participants, however none reported on the effectiveness of the recruitment approaches used or factors influencing participation (Cederlund, Hagberg, Billstedt, I. Gillberg, & C. Gillberg, 2008;Gerber et al, 2011;Madriaga, 2010).…”
Section: Engaging Adults With Asd In Longitudinal Researchmentioning
confidence: 99%